2022
DOI: 10.25122/jml-2021-0293
|View full text |Cite
|
Sign up to set email alerts
|

Management of antibacterial therapy of infectious and inflammatory diseases of the urinary tract in children and regional peculiarities during the COVID-19 pandemic

Abstract: Urinary tract infections (UTIs) remain an urgent issue in clinical pediatrics. Empirical selection of antibacterial therapy becomes more complicated, and antibacterial drug indication is not always clinically substantiated. This study aimed to compare the antibacterial susceptibility pattern of the main group of urinary tract infectious agents from 2009–2016 with intermediate results from 2020–2021, during the COVID-19 pandemic, among children in the Chernivtsi region. Urine samples were collected from 3089 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In contrast to our findings, Zeshan et al [ 48 ] reported that isolated strains of K. pneumoniae in 88%, P. aeruginosa in 75%, and S. aureus in 45% of cases were resistant to ciprofloxacin. Other researchers also noted that there is high resistance to fluoroquinolone and cephalosporins among the gram-negative bacteria isolated from the COVID-19 patients [ 41 , 49 ]. This may be a reflection of the widespread use of these medications for empirical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, Zeshan et al [ 48 ] reported that isolated strains of K. pneumoniae in 88%, P. aeruginosa in 75%, and S. aureus in 45% of cases were resistant to ciprofloxacin. Other researchers also noted that there is high resistance to fluoroquinolone and cephalosporins among the gram-negative bacteria isolated from the COVID-19 patients [ 41 , 49 ]. This may be a reflection of the widespread use of these medications for empirical therapy.…”
Section: Discussionmentioning
confidence: 99%